Occupational transition and country-of-origin effects in the early stage occupational assimilation of immigrants: some evidence from Australia - Kostenko, W.; Harris, Mark; Zhao, X. (Taylor & Francis, 2012)
We examine the occupational attainment of recent immigrants at 2 yearspost migration in order to study their early stage assimilation into thelabour market in Australia. Human capital endowments and country-oforigineffects are examined for six occupational groups. We also studytransitions across occupations from source to host country. The empiricalapproach utilizes the Ordered Generalized Extreme Value (OGEV) modelwhich embodies differing utility functions across occupational outcomes,as well as accounting for any ordering in these outcomes. The resultssuggest that the transferability of knowledge and skills is affected bycultural and social backgrounds, and that non-Western immigrants aredisproportionately channelled into inferior jobs post migration. Theinvestigation of the country-of-origin effect on the skilled migrants’occupational transition process is especially apt in the context of skillshortages in many host countries.